Improved Design of MW-level Wind Turbine Electrical System for High Altitude - 许雄伟; 姚辉 (Kongzhi Yu Xinxi Jishu)
The influences of the high altitude climate to MW-level wind turbine electrical system are analyzed, and the solutions of WT1650 variable speed constant frequency doubly-fed wind turbine(1.65 MW)running at the altitude of 4 000 m are proposed. Then the improved design is made to its electrical system, which provides some guidance to the conventional wind turbine working in high altitude.